2015
DOI: 10.1155/2015/612580
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiography Imaging in Targeted Alpha Therapy with Timepix Detector

Abstract: There is a lack of data related to activity uptake and particle track distribution in targeted alpha therapy. These data are required to estimate the absorbed dose on a cellular level as alpha particles have a limited range and traverse only a few cells. Tracking of individual alpha particles is possible using the Timepix semiconductor radiation detector. We investigated the feasibility of imaging alpha particle emissions in tumour sections from mice treated with Thorium-227 (using APOMAB), with and without pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Its utility in detecting β-particles from a Carbon-14 ( 14 C) sample showed that Timepix was highly sensitive with a minimum detectable activity of 0.0077 Bq and with a spatial resolution of 76.9 μm at full-width at half-maximum (FWHM; Esposito et al, 2011a , b ). In another study, Timepix was used to measure α-particle emissions in tumor sections from mice treated with chemotherapy and a radiolabeled DAB4 murine monoclonal antibody [thorium-227 ( 227 Th)-APOMAB] ( Darwish et al, 2015 ). Results showed that the α-particle emissions could be visualized and quantified using the detector ( Miller, 2018 ).…”
Section: Methods To Detect the Spatial Distribution Of Radionuclidesmentioning
confidence: 99%
“…Its utility in detecting β-particles from a Carbon-14 ( 14 C) sample showed that Timepix was highly sensitive with a minimum detectable activity of 0.0077 Bq and with a spatial resolution of 76.9 μm at full-width at half-maximum (FWHM; Esposito et al, 2011a , b ). In another study, Timepix was used to measure α-particle emissions in tumor sections from mice treated with chemotherapy and a radiolabeled DAB4 murine monoclonal antibody [thorium-227 ( 227 Th)-APOMAB] ( Darwish et al, 2015 ). Results showed that the α-particle emissions could be visualized and quantified using the detector ( Miller, 2018 ).…”
Section: Methods To Detect the Spatial Distribution Of Radionuclidesmentioning
confidence: 99%
“…19 The Timepix radiation detector 20 has the ability to identify individual radiation particles including photons (x-rays or gamma rays), electrons, and alpha particles. [21][22][23][24][25][26] Our previous study confirmed that Timepix could be used to detect and quantify spatial distribution of alpha particles, electrons, and x-rays resulting from thorium-227 (Th-227) decay in tumor sections from mice treated with a Th-227-labeled antibody. 26 These features along with the ability of Timepix to measure deposited energy suggest that Timepix could be used to estimate absorbed dose in targeted alpha therapy.…”
Section: Introductionmentioning
confidence: 85%
“…The La-specific monoclonal antibody, DAB4 (also known as APOMAB ® ) was demonstrated to be able to specifically target dead tumor cells in vivo 143 , and targetability was augmented after DNA-damaging treatment81., 82., 143., 144.. A recent study further demonstrated the selectivity of DAB4 for chemotherapy-induced dead tumor cells and this postchemotherapy selectivity was related to a relative increase in the availability of DAB4-binding targets in tumor tissue rather than in normal tissues 115 , which provided further evidence to support the diagnostic use of DAB4 as a predictive marker of treatment responses.…”
Section: Molecular Imaging and Therapeutic Strategies Targeting Necromentioning
confidence: 99%